Expression of JCAD and EGFR in Perineurial Cell–Cell Junctions of Human Inferior Alveolar Nerve - Hiraoka, Yujiro; Matsumura, Megumi; Kakei, Yasumasa; Takeda, Daisuke; Shigeoka, Manabu; Kimoto, Akira; Hasegawa, Takumi; Akashi, Masaya (The journal of histochemistry and cytochemistry, 2023)
Although perineurium has an important role in maintenance of the blood–nerve barrier, understanding of perineurial cell–cell junctions is insufficient. The aim of this study was to analyze the expression of junctional cadherin 5 associated (JCAD) and epidermal growth factor receptor (EGFR) in the perineurium of the human inferior alveolar nerve (IAN) and investigate their roles in perineurial cell–cell junctions using cultured human perineurial cells (HPNCs). In human IAN, JCAD was strongly expressed in endoneurial microvessels. JCAD and EGFR were expressed at various intensities in the perineurium. In HPNCs, JCAD was clearly expressed at cell–cell junctions. EGFR inhibitor AG1478 treatment changed cell morphology and the ratio of JCAD-positive cell–cell contacts of HPNCs. Therefore, JCAD and EGFR may have a role in the regulation of perineurial cell–cell junctions.